Assessment of post exposure anti-rabies therapy in cattle - Rishi Keshavan (Department of Epidemiology and Preventive Medicine, College of Veterinary and Animal Sciences, 2005)
The immune response and efficacy of two different anti-rabies vaccines in two different post exposure schedules were studied in rabies exposed cattle. An inactivated tissue culture anti-rabies vaccine (Raksharab) and a DNA combined tissue culture inactivated anti-rabies vaccine (Dinarab) were used. The study animals were grouped in to four groups. Animals of group I and III were vaccinated with inactivated tissue culture anti-rabies vaccine (Raksharab) with schedule I (injection of vaccine on 0, 3rd, 7th, 14th and 28th days) and schedule II (administration of five doses of vaccine on 0, 1st, 2nd,3rd and 4th days continuously) respectively and animals of group II and IV were vaccinated with DNA combined tissue culture inactivated anti-rabies vaccine (Dinarab) with schedule I and schedule II respectively. The rabies virus neutralizing antibody titers were assessed on day zero, 7th, 14th, 28th, 60th and 90th days of post vaccination by employing Rapid fluorescent focus inhibition test - (RFFIT).